2022
DOI: 10.1177/23743735221092545
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Environmental Stressors on Patient Experience in Medical, Surgical, and COVID-19 Intensive Care Unit

Abstract: This study was conducted to evaluate the effects of environmental stressors on patients’ intensive care experiences in medical, surgical, and COVID-19 intensive care units (ICUs). The sample group consisted of 231 patients hospitalized in medical and surgical ICUs and agreed to participate in the study. The data analysis was performed with IBM SPSS Statistics 25. The average age of the patients was 53.67 ± 13.3, 55.4% were male, 47.6% were high school graduates, and 45.5% were followed up in the COVID-19 ICU. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…In surgical patients, stress has devastating effects such as increased pain, impaired wound healing, and prolongation of hospital stay. [21][22][23] In our study, the patients' PSS total mean score was 26.7 ± 3.76. Long hospital stay, presence of cannula, tube and catheter, immobilisation, multiple drug use, noise and sleep problems are sources of stress in hospitalised patients.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…In surgical patients, stress has devastating effects such as increased pain, impaired wound healing, and prolongation of hospital stay. [21][22][23] In our study, the patients' PSS total mean score was 26.7 ± 3.76. Long hospital stay, presence of cannula, tube and catheter, immobilisation, multiple drug use, noise and sleep problems are sources of stress in hospitalised patients.…”
Section: Discussionmentioning
confidence: 52%
“…We found a negative, strong and statistically significant correlation between perceived stress and body image ( P < 0.05). In surgical patients, stress has devastating effects such as increased pain, impaired wound healing, and prolongation of hospital stay 21‐23 . In our study, the patients' PSS total mean score was 26.7 ± 3.76.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…There was a phenomenon relating to the unknown prognosis of the disease and environmental stressors (Gezginci et al, 2022), which suggested that the environmental stressors in the ICU were high and the patients were at risk from anxiety and depression. Bulbuloglu et al (2022) suggested that the environmental stressors created an emotionally exhausting negative perception in the patient. As a result, most patients experienced a difficult time during their isolation due to physical problems, loneliness, and separation from their families (Galehdar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%